2022
DOI: 10.1111/head.14384
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of thiamine and riboflavin in relation to severe headache or migraine: A cross‐sectional survey

Abstract: Objective The purpose of this study was to identify the prevalence of severe headache or migraine and the association between dietary thiamine and riboflavin intake with headache history using a large, nationally representative population sample. Background Severe headache and migraine are common and disabling neurological disorders worldwide. Previous studies revealed that the B vitamin group, as an important nutrient of diet, can reduce migraine disability. Methods We performed a cross‐sectional study of Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In 2015, Menon et al had already explored dietary folate intake and clarified its negative association with headache frequency (23) . There were also other nutrients that have been extensively investigated, among them vitamin B 2 (riboflavin) and co-enzyme Q10 supplementation which have been shown to be beneficial for migraine patients (19,24) . Headache may be associated with hyperhomocysteinaemia (25) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, Menon et al had already explored dietary folate intake and clarified its negative association with headache frequency (23) . There were also other nutrients that have been extensively investigated, among them vitamin B 2 (riboflavin) and co-enzyme Q10 supplementation which have been shown to be beneficial for migraine patients (19,24) . Headache may be associated with hyperhomocysteinaemia (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Various potential covariates were assessed based on previous literature (18)(19)(20) . Demographic covariates included age, gender, ethnicity, education level, marital status and family income, all of which were obtained through self-expression during the interview process.…”
Section: Potential Covariatesmentioning
confidence: 99%
“…The current paper by Li et al suggests ways to address both the "why" of migraine and the "how to" of treating the disorder. 1 The authors make use of a nationwide population-based survey to analyze the correlation between dietary intake of two essential substances, thiamine and riboflavin, and reduced burden of headache, likely migraine, in a large and diverse population, controlling for other factors already known to influence an individual's risk of migraine (sex, race, socioeconomic status, and education).…”
Section: G U E S T E D I T O R I a L B1 And/or B2? That Is The Questionmentioning
confidence: 99%
“…Two cross‐sectional studies examining the results from the National Health and Nutrition Examination Survey (NHANES 1999–2004) in relation to headaches have been conducted recently. The first assessed thiamine and riboflavin intake and reported that individuals with higher thiamine intake had reduced odds of headache, while no significant reduction in headache was seen with higher riboflavin intake 7 . The second examined magnesium and reported that inadequate dietary magnesium intake was associated with a higher likelihood of having migraine in adults 8 …”
mentioning
confidence: 99%
“…The first assessed thiamine and riboflavin intake and reported that individuals with higher thiamine intake had reduced odds of headache, while no significant reduction in headache was seen with higher riboflavin intake. 7 The second examined magnesium and reported that inadequate dietary magnesium intake was associated with a higher likelihood of having migraine in adults. 8 Further, hunger is a well-known trigger for headaches.…”
mentioning
confidence: 99%